The effect of alexithymia on depression: evidence from meta-analysis - Liu, Zhijun; He, Shiwei; Hou, Chunna (Frontiers in Psychology, 2025)
IntroductionDepression is primarily characterized by persistent low mood and cognitive dysfunction, whereas whereas alexithymia refers to difficulties in cognitively processing emotions. Although alexithymia being recognized as a risk factor for depression, there is no clear scholarly consensus on its exact role.MethodsThis investigation employs a meta-analytic random effects model to examine the relationship between alexithymia and depression. The analysis draws on data from 35 studies involving 23,085 individuals.ResultsSeveral key findings are revealed: Firstly, the total alexithymia score shows a positive correlation with depression severity, possibly influenced by cultural differences between Eastern and Western populations. Secondly, Difficulty in Describing Feelings (DDF) and Difficulty in Identifying Feelings (DIF) are significantly associated with depression, while Externally Oriented Thinking (EOT) has a weaker link. Thirdly, the relationship varies across different demographic groups and depends on the depression assessment tool used.DiscussionThese results emphasize the importance of examining not only the overall relationship between alexithymia and depression but also its specific dimensions. Additionally, the study explores the rational explanation of the interplay between alexithymia and depression within a Chinese cultural context and within the framework of the interpersonal theory of depression.